DEPOSISI LAPISAN TIPIS ZINC OXIDE (ZnO) DI ATAS SUBSTRAT KACA DENGAN METODE SOL-GEL UNTUK APLIKASI DEGRADASI WARNA - Marediyanti Pusvitasari; Heri Sutanto (Youngster Physics Journal, 2012)
ABSTRACT Zinc oxide (ZnO) thin films have been successfully deposited on glass substrates by spray coating method with a variety of the coating of volume about 10 ml to 50 ml. Then ZnO thin films used to degrade 10 ppm methylene blue dyes with sunlight as a medium. ZnO solution was synthesed by dissolving zinc acetate dehydrate (Zn (COOCH3) 2.2H2O into a solvent of isopropanol ((CH 3) 2CHOH) and monoethanolamine (MEA: HOCH2CH2NH2) at room temperature with a concentration of 0.3 M of zinc acetate and the molar ratio of MEA and ZnAc is 1:1. Then the solution was stirred by a magnetic stirrer at a temperature of 70 ° C for 30 minutes to obtain a clear and homogeneous solvent. Furthermore, gel of ZnO is placed on a spray hole and sprayed on a glass substrate that has been heated to a temperature of 250oC. This ZnO thin films then sintering at a temperature of 400oC for 1 hour. The ability of photocatalyst of ZnO for degradation of methylene blue color was observed through the elektrooptis measurement using polarisator and absorbance test using UV-Vis to obtain the percentage of color degradation. The test results of EDX showed that the ZnO thin film having an atomic composition of 50.27% Zn and 49.73% O. And the test results of elektrooptis showed that a thin film with volume coating of 50 ml, is the highest transmission intensity. This suggests that free radicals that more contained in the solvent. A high percentage of color degradation also obtained by stirring the solvent. Keywords: ZnO thin film, spray coating, Sol gel, color degradation